Hubungan Antara Efikasi Akademik, Prokrastinasi Dan Kemandirian Belajar Dengan Hasil Belajar Geografi Siswa SMA Negeri Di Kota Malang - Nisa'i Choiriyah, Zauharotu; Hari Utomo, Dwiyono; Rosida, Fatiya; Suharto, Yusuf (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
The learning methods changed due to Covid-19, the government originally set online learning to be a limited face-to-face meeting using the hybrid learning method. The hybrid learning method in implementation requires a high level of academic efficacy, suppressing procrastination and a high level of learning independence. The purpose of this study is to determine the relationship between (1) academic efficacy with student geography learning outcomes, (2) procrastination with student geography learning outcomes, (3) learning independence with student geography learning outcomes and (4) academic efficacy, procrastination and learning independence with student geography learning outcomes. The design of this study is correlational ex post-facto quantitative approach. The sampling technique used the cluster sampling technique with the slovin formula and obtained a sample of 244. Data collection techniques use questionnaires and documentation. The results of a simple correlation test and a multiple linear correlation test of each independent variable show that there is a relationship with the dependent variable. By knowing the level of academic efficacy, procrastination and student learning independence, it can also monitor the causes that affect student geography learning outcomes.